(untitled) (Biocenosis, 2015)
The ocean is a resource rich in microorganisms that can produce a great variety of compounds such as biosurfactants. In Costa Rica, it has been determined that the development of studies and applications of these compounds are scarce. For instance, this study pretends to make prospective activities with bacterial strains extracted from the Nicoya Gulf, and select the ones that can produce biosurfactants. Three strains were extracted from their natural environment, were identified and were grown in marine agar. Then, they were purified and the resultant biosurfactant was obtained using whether or not corn oil. Also the biosurfactant activity was evaluated with the kerosene detection technique. The index emulsion (E24) and hemolitic activity of the three strains were determined. Two of the strains were identified as Pseudomona aeruginosa; they also presented biosurfactant activity but no hemolytic activity. The other strain was identified as Aeromonas hyla, and presented hemolytic activity opposing the two other strains. This type of response might be because A. hyla probably did not accomplish its maximum stage of activity and it did not complete its stage of adaptation and acclimatization. Pseudomonas aeruginosa; Aeromonas hyla; Microorganisms; Biosurfactants